2013
DOI: 10.1111/j.1464-410x.2012.11773.x
|View full text |Cite
|
Sign up to set email alerts
|

Genital lichen sclerosus/balanitis xerotica obliterans in men with penile carcinoma: a critical analysis

Abstract: What's known on the subject? and What does the study add?• The European Association of Urology guidelines identify lichen sclerosus (LS) as a strong risk factor for penile squamous cell carcinoma (pSCC). However, this statement is based on the findings of case-control studies (Level of Evidence 2a) and a direct causal relationship between LS/balanitis xerotica obliterans (BXO) and pSCC remains to be established. Firm guidelines with respect to the appropriate follow-up policy for LS/BXO are lacking, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 33 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…Importantly while many cases can be managed (although not often cured) with topical steroids or minor surgical procedures, 4 as many as 5% of cases will be associated with local malignancy (vulvar cancer in women, penile/urethral cancer in men). 5,6 More commonly, males with LS are affected by urethral stricture disease, present in nearly 30% of cases. 7,8 LSUSD can be recalcitrant to conventional treatments and often necessitates urinary diversion.…”
mentioning
confidence: 99%
“…Importantly while many cases can be managed (although not often cured) with topical steroids or minor surgical procedures, 4 as many as 5% of cases will be associated with local malignancy (vulvar cancer in women, penile/urethral cancer in men). 5,6 More commonly, males with LS are affected by urethral stricture disease, present in nearly 30% of cases. 7,8 LSUSD can be recalcitrant to conventional treatments and often necessitates urinary diversion.…”
mentioning
confidence: 99%
“…7,11 The European Association of Urology guidelines identify MGU-LS as a strong risk factor for penile cancer. 12 Despite the aforementioned incidence and recommendation, only 48.9% of AUA members reported counseling men on the associated risks of cancer following MGU-LS diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…LS can occur in phimosis,28 which in itself is a risk factor for penile SCC 6–8 51 52. Retrospective studies have demonstrated that LS can occur in conjunction with squamous hyperplasia (SH) and differentiated PeIN and is typically seen with non-HPV related penile SCC such as the conventional, keratinising subtype 28 31 32 53 54. One study from Belgium (n=76) found a similar rate of LS in association with both HPV and non-HPV penile SCC,55 and concluded the role of LS was unclear in penile SCC.…”
Section: Dermatoses Associated With Penile Squamous Cell Carcinomamentioning
confidence: 99%